Use of Battery Carbon as Electrodes in Arc Discharge Method for Fabrication of Carbon-Modified TiO2. - Isya Fitria Andhika; Carissa Hertiningtyas; Ardian Aji; Alifia Desy; Teguh Endah Saraswati; Patiha Patiha (UNIVERSITAS SEBELAS MARET (UNS), 2016)
Fabrication with carbon-modified TiO2 by arc discharge method in liquid medium has been studied. This research was performed in two steps including fabrication and characterization. This fabrication was done by arcdischarge method with graphite electrodes from dry cell batteries and liquid medium suspension of TiO2 in ethanol 30, 50 and 70 %. A strong current was applied to electrode as 10 -50 A (20-40 V). Nanocomposites formed on the liquid medium surface were collected and characterized using X-ray diffraction (XRD),scanning electron microscope (SEM) dan energy dispersive spectroscopy (EDS) to determine crystallinity, surface morphology and the constituent elements, respectively. XRD data shows that the most effective fabrication TiO2/Karbon by liquid medium in ethanol 50 % indicated from the formation of a new peak with high intensity of TiC on 2Ɵ= 36.02 °. SEM data shows that the morphology of each aggregated TiO2/Karbon compared to the morphology of TiO2. In addition, EDS data shows the presence of the element carbon, titanium and oxygen in the same area indicating that the successful formation of composite material between TiO2 dan carbon.